2020
DOI: 10.5433/1679-0359.2020v41n5supl1p2219
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in canine hematological parameters after commercial feed feeding

Abstract: Complete blood count (CBC) is the evaluation of blood cells, which provides resourceful information. Considering that inadequate fasting time is the most common pre-analytical error in laboratory diagnosis and is associated with lipemia in blood samples, which has not yet been adequately investigated in dogs, this study aimed to assess diurnal postprandial changes in the CBC of healthy dogs fed with industrialized feed. Eighteen clinically healthy dogs aged 2-6 years and weighing over 6 kg were enrolled in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
5
7
0
Order By: Relevance
“…In humans with samples also obtained at the same day before and after the meal, the decrease seen on these parameters was attributed to fluid intake during the meal (LIPPI et al, 2010, p. 98). As pointed out by Costa et al (2020Costa et al ( , p. 2226, the reduction of the RBC series concentration in dogs following feeding could also be related to water intake. In the present study, the analysis was carried out in a timely manner at the same time of the day, with no interference from water intake by successive collections at the same day or the same effect of the circadian cycle, which therefore explains the discrepancies.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In humans with samples also obtained at the same day before and after the meal, the decrease seen on these parameters was attributed to fluid intake during the meal (LIPPI et al, 2010, p. 98). As pointed out by Costa et al (2020Costa et al ( , p. 2226, the reduction of the RBC series concentration in dogs following feeding could also be related to water intake. In the present study, the analysis was carried out in a timely manner at the same time of the day, with no interference from water intake by successive collections at the same day or the same effect of the circadian cycle, which therefore explains the discrepancies.…”
Section: Discussionmentioning
confidence: 85%
“…Red blood cells concentration and therefore HCT were not influenced by feeding. Previous studies in dogs, with blood samples obtained during a 12 h period after feeding reported a decrease in these parameters and hemoglobin since 1 h following the meal (COSTA et al, 2020(COSTA et al, , p. 2224. In humans with samples also obtained at the same day before and after the meal, the decrease seen on these parameters was attributed to fluid intake during the meal (LIPPI et al, 2010, p. 98).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations